Hubungan Tingkat Pengetahuan Gizi Dengan Kebiasaan Makan dan Aktivitas Fisik pada Remaja Siswa SMA N 04 Kotabumi Kecamatan Kotabumi Selatan Kabupaten Lampung Utara Tahun 2024 - Pradipta, Nadila Ajeng; Nurhartanto, Adhi; Saleh, Asep Jalaludin (CV. Rayyan Dwi Bharata, 2025)
Nutritional knowledge is important for choosing foods that not only meet the body's needs but also prevent diseases. Nutritious food contains water, protein, fat, carbohydrates, as well as vitamins and minerals that are often affordable. According to Rikesdas data from 2018, it shows that among teenagers aged 15 to 19, 41% consume sweet foods, 58.43% consume sweet drinks, and 43.8% consistently consume fatty foods, high-cholesterol foods, or fried foods more than once a day. The aim is to understand how the level of nutritional knowledge, eating habits, and physical activity of students at SMA N 04 Kotabumi are interconnected. The research design uses a cross-sectional approach and is quantitative in nature. In this study, a Simple Random Sampling technique was used, and the sample consisted of 75 respondents from SMA N 04 Kotabumi. A p-value of 0.001 ( 0.05) indicates a significant association between nutritional knowledge and eating habits. Meanwhile, a p-value of 0.019 ( 0.05) shows a significant relationship between nutritional knowledge and physical activity.